Characterization and formation mechanisms of viable, but putatively non-culturable brewer's yeast induced by isomerized hop extract. (1st February 2022) - Xiao, Yang; Wang, Zengyan; Sun, Weizhe; Luan, Yingjia; Piao, Meizi; Deng, Yang
Abstract: In this study, the formation and resuscitation of a viable, but putatively non-culturable (VPNC) brewer's yeast under various concentrations of isomerized hop extracts were investigated. The isomerized hop extract (300 mg/L) treatment for 2 h completely induced yeast cells into the VPNC state. The VPNC cells incubated on YPD agars containing catalase (2500 U/plate) recovered their culturability within three days. Notably, the VPNC yeast had significantly lower fermentation efficiency during wort fermentation than the normal yeast, yielding lower ethanol contents. Beer produced by the VPNC yeast contained significantly fewer aromatic alcohols and esters. However, no significant differences were observed in the fermentation performance and the formation of flavor volatiles between the normal and resuscitated yeast. Our transcriptomic analysis further showed that the genes involved in the carbohydrate and amino acid metabolism, DNA replication, and cell division were downregulated in VPNC cells. Conversely, the TCA cycle, ABC transporter, organic acid metabolism, and oxidoreductase activities were increased. Moreover, we confirmed that Yap1 gene deletion suppressed the entry of yeast cells into the VPNC state. Overall, the increased survival ability, inhibited cell division, and reduced metabolic activity in the yeast might lead to the induction of an isomerized hop extract-induced VPNC state. Highlights: This study is the first to reveal VPNC S. cerevisiae occurrence induced by isomerized hop extract. Catalase addition is an effective method for culturability recovery of VPNC S. cerevisiae. The VPNC yeast had lower fermentation efficiency and fewer flavor volatiles than the normal yeast. The isomerized hop extract-induced VPNC state formation might be due mainly to oxidative stress. The deletion of the Yap1 gene suppressed the entry of the yeast cells into the VPNC state.